The effect of palatine tonsil size on occlusion among 10- 12 years students in erbil city. - Hozan Farid Tawfiq; Omar Fawzi Chawshli (Erbil Dental Journal)
Background and objectives: The effect of the palatine tonsil size in the development of dental intra-arch and inter-arch abnormalities is often brought up in the literature, but it remains controversial. Data on the possibility of a relationship between enlarged tonsils and the occurrence of malocclusions are subjective. The purpose of this study was to seek an association between the space occupied by the palatine tonsils and the dental arch measurements. Methods: A cross-sectional study was performed in Erbil city on a group of primary school students aged (10-12) years old. A tonsillar examination was performed for each student and graded according to the standardized tonsillar hypertrophy grading scale. A sample size of (300) students, (160) male and (140) female was randomly selected. Dental impressions were taken for each student. Data were analyzed with SPSS program version 22. Comparisons of qualitative variables according to tonsillar grade and gender and the relation of tonsillar grade according to gender were made using the chi-square test. The strength of the association between tonsillar grade and qualitative variables was evaluated with a phi coefficient (φ). The strength of the association between tonsillar grade and quantitative variables was assessed by Spearman's rank correlation coefficient (rho). The association between gender and quantitative variables was evaluated by t-test. The significance threshold was set at P ≤ 0.05. Results: Results showed that there was a significant and positive relation between Angle's molar relationship, overjet, and palatine tonsil size but no significant difference in palatine tonsil size according to males and females. Conclusions: Early evaluation of the size of the palatine tonsils by the pedodontist would help prevent orthodontic abnormalities caused by upper airway obstruction during childhood.